The Addition of Sweet Potato Varieties Cilembu as a Prebiotics to Increase Growht of Catfish (Pangasius sp.) - Iin Inayati (JURNAL PERIKANAN DAN KELAUTAN, 2015)
This study aimed to evaluate the role of sweet potato varieties as a source of prebiotic cilembu in catfish feed. The experiment were done with four treatments and three replicates, are treatment A (prebiotic 0%), B (prebiotic 0.5%), C (prebiotic 1%) and D (prebiotic 1.5%). Fish were fed three time daily in at satiation. The results showed that addition of prebiotics 0.5% on commercial diets can increase the value of the number of bacteria population was 9.42±0.03 log CFU/ ml, protein retention was 28.51±4.91%, lipid retention was 70.60±13.17%, protein efficiency Ratio (PER) was 137.93±22.06%, Specific Growth Rates (SGR) was 1.81±0.20%, feed efficiency was 36.10±5.77% and Survival Rate (SR) was 97.78±3.85%.